The use of multiparametrer biofeedback to a patient with consequences of craniocerebral injury - G. M. Tsirkin; Ye. V. Nechayev; Ye. N. Nechayeva (Бюллетень сибирской медицины, 2010)
The paper describes the clinical effects of the 9-months course of biofeedback-based treatment of a patient with tetraparesis. As a result of treatment a significant improvement of the conditions was registered.